Integrating Digital Literacy and Character Education to Foster Digital Citizenship in Primary Schools: A Society 5.0 Perspective - Kartika Yuni Purwanti; Zulmi Roestika Rini; Ela Suryani; Suhirno Suhirno; Hesti Yunitiara Rizqi; Anni Malihatul Hawa (Proceeding International Collaborative Conference on Multidisciplinary Science, 2026)
The Society 5.0 era requires primary education to balance technological advancement with the development of students' moral and social values. Although digital literacy has become an essential competency, many primary schools still implement it separately from character education, limiting students' ability to develop responsible digital behavior. This study aimed to examine how digital literacy and character education can be integrated to foster digital citizenship among primary school students. A qualitative case study was conducted in selected primary schools implementing Society 5.0-oriented learning. Data were collected through semi-structured interviews with teachers, classroom observations, and document analysis, and were analyzed using thematic analysis. The findings identified three key strategies for promoting digital citizenship: integrating digital ethics into subject learning, implementing collaborative project-based learning to strengthen digital empathy and responsible online behavior, and fostering active partnerships between schools and families to reinforce digital character development. The integrated approach contributed to improved ethical awareness, responsible technology use, collaborative skills, and the prevention of cyberbullying among students. The study concludes that integrating digital literacy with character education provides an effective pedagogical framework for preparing responsible, ethical, and digitally competent citizens capable of thriving in the Society 5.0 era.